2016
DOI: 10.3375/043.036.0108
|View full text |Cite
|
Sign up to set email alerts
|

Release of Suppressed Red Spruce Using Canopy Gap Creation—Ecological Restoration in the Central Appalachians

Abstract: Issue: Historic harvest of red spruce and related disturbance in the central and southern Appalachians has resulted in large losses of soil organic carbon into the atmosphere as CO 2 . Recent studies suggest that restoring red spruce with targeted forest management plans could restore significant parts of this carbon within a century while also improving regional habitat for threatened wildlife and ecosystem services like drinking water security. Red spruce and similar species promote soil carbon buildup: Man… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(40 citation statements)
references
References 43 publications
1
39
0
Order By: Relevance
“…In this study, we were able to observe the conditions that favor spruce presence as well as those associated with important red spruce characteristics within an unmanaged, second-growth forest. Spruce regeneration in previous studies has been shown to establish under variable light conditions (Greenwood et al, 2008;Mayfield and Hicks, 2010;Potheir and Prevost, 2008) and respond positively to increases in light availability (Moores et al, 2007;Olson et al, 2014;Rentch et al, 2016). The relationship between spruce seedling establishment and seed source proximity has also been illustrated (Beach and Halpern, 2001;Cavallin and Vasseur, 2009;Hughes and Bechtel, 1997) suggesting higher seedling densities within shorter distances from seed sources.…”
Section: Discussionmentioning
confidence: 91%
See 3 more Smart Citations
“…In this study, we were able to observe the conditions that favor spruce presence as well as those associated with important red spruce characteristics within an unmanaged, second-growth forest. Spruce regeneration in previous studies has been shown to establish under variable light conditions (Greenwood et al, 2008;Mayfield and Hicks, 2010;Potheir and Prevost, 2008) and respond positively to increases in light availability (Moores et al, 2007;Olson et al, 2014;Rentch et al, 2016). The relationship between spruce seedling establishment and seed source proximity has also been illustrated (Beach and Halpern, 2001;Cavallin and Vasseur, 2009;Hughes and Bechtel, 1997) suggesting higher seedling densities within shorter distances from seed sources.…”
Section: Discussionmentioning
confidence: 91%
“…Lhotka et al (2018), examined the effects of gap size on species composition and volume increases over fifty years in oak stands and found that species diversity and growth were significantly reduced in light limited small gaps (200 m 2 ). The effects of gap size on regeneration species composition, survival, light availability, seedling density, and growth responses are well documented (Brokaw, 1985;Dumais and Prevost, 2016;Nakashizuka, 1984;Qinghong and Hytteborn, 1991;Rentch et al, 2016;Wu et al, 1999). Changes in irradiance have large impacts on seedling development and growth (Gilbert et al 2001;Denslow 1987).…”
Section: Light Regimesmentioning
confidence: 99%
See 2 more Smart Citations
“…Historic documentation suggests that much of the central Appalachians were covered with red spruce forests, but extensive logging and wildfires decimated the population (Allard and Leonard, 1952;. Both governmental and non-governmental agencies are attempting to restore red spruce ecosystems in the central Appalachians (CASRI, 2017), so information on where these ecosystems existed historically, and where they are most likely to succeed today is needed (Rentch et al, 2016).…”
Section: Introductionmentioning
confidence: 99%